Mycobacterium haemophilum osteomyelitis: case report and review of the literature - Read Ron; Elsayed Sameer (BMC Infectious Diseases, 2006)
Abstract Background Mycobacterium haemophilum is a slow-growing, fastidious, iron-requiring microorganism that, relative to other non-tuberculous mycobacterial species, has rarely been documented as a cause of human infection. This microorganism appears to be acquired via environmental exposure although its natural habitat and mode of acquisition are unknown. It has primarily been implicated as a cause of ulcerating cutaneous or subcutaneous nodular skin lesions, particularly in immunocompromised patients, although infections at extracutaneous sites have also been described. Osteomyelitis, while rarely documented, appears to be an important complication of infection with M. haemophilum in these patients. Case presentation We describe a unique case of culture-confirmed M. haemophilum osteomyelitis in an adult woman with polycythemia vera and review the world literature on bone infections due to this organism. Conclusion Mycobacterium haemophilum is an important but infrequently encountered cause of osteomyelitis in immunocompromised patients, often requiring months to years of medical therapy, with or without surgery, to effect a clinical cure.